Influences of latent heat storage heat sink integrated with solar dryer to enhance drying period - Nakum Divyangkumar; Sudhir Jain; N.L. Panwar (Energy Nexus, 2022)
Drying is an important procedure and is popular among farmers to dry agricultural produce. However, farmers cannot dry their crops due to the limited availability of sun rays during the daytime. Because of the above issue, a solar-operated heat sink unit was designed and developed to store 40 kg of phase change material (PCM) for latent heat storage, enabling the desired drying temperature for continuous drying operation. Barium Hydroxide Octahydrate [Ba(OH)2. 8H2O] was used as a PCM which can store the energy in the daytime and release it during off-sunshine hours. The performance of PCM integrated with a solar dryer was investigated with a drying of potato chips in terms of thermal efficiency, drying rate, drying efficiency, and heat utilization factor. In the PCM-enabled dryer, the product was dried in a single day, maintaining the average drying temperature between 58 °C to 66 °C throughout the drying. In contrast, the same product was dried in next day in case of open sun drying. The developed drying system is positioned to operate effectively 4-5 hours after sunset and found a viable option for Agri industries and domestic purposes as it is nonpolluting to the environment and does not contain many more conventional energy sources. Moreover, the developed system saved 5604 kWh of electrical energy and 555.06 liters of diesel fuel each year, as well as reduced 5.49 t CO2 emissions.